1984
DOI: 10.1002/j.1460-2075.1984.tb02189.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the guanine nucleotide regulatory protein Ni mediate progesterone inhibition of Xenopus oocyte adenylate cyclase?

Abstract: In Xenopus laevis oocytes progesterone is able to inhibit directly the plasma membrane adenylate cyclase activity and induce reinitiation of meiotic maturation. To determine whether progesterone inhibition is mediated by the inhibitory guanine nucleotide‐binding regulatory component of adenylate cyclase, Ni, the effect of the Bordetella pertussis toxin (IAP) and limited proteolysis on progesterone action in oocytes was investigated. Treatment of oocyte membranes with islet activating protein (IAP) in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The non-genomic mechanism, through which progesterone triggers meiosis resumption, is not completely understood, however it is well established that at a very early step of the process, which takes place at the plasma membrane, inhibition of the enzyme AC occurs (Maller et al, 1979;Bravo et al, 1978;Schorderet-Slatkine et al, 1978;Jordana et al, 1984). Progesterone induced AC inhibition has been shown to be GTP dependent and requires the participation of a Pertussis toxin insensitive G-protein (Jordana et al, 1981a(Jordana et al, ,b, 1984Goodhardt et al, 1984;Olate et al, 1984;Sadler et al, 1984;Olate et al, 1985). In addition, AC activity stimulated by positive G-protein modulators such as Gpp(NH)p, GTPgS, aluminum fluoride and Cholera toxin, is inhibited by progesterone, pointing out to the participation of a Gsa type of G-protein (Jordana et al, 1981a(Jordana et al, , 1984Sadler and Maller, 1981).…”
mentioning
confidence: 95%
“…The non-genomic mechanism, through which progesterone triggers meiosis resumption, is not completely understood, however it is well established that at a very early step of the process, which takes place at the plasma membrane, inhibition of the enzyme AC occurs (Maller et al, 1979;Bravo et al, 1978;Schorderet-Slatkine et al, 1978;Jordana et al, 1984). Progesterone induced AC inhibition has been shown to be GTP dependent and requires the participation of a Pertussis toxin insensitive G-protein (Jordana et al, 1981a(Jordana et al, ,b, 1984Goodhardt et al, 1984;Olate et al, 1984;Sadler et al, 1984;Olate et al, 1985). In addition, AC activity stimulated by positive G-protein modulators such as Gpp(NH)p, GTPgS, aluminum fluoride and Cholera toxin, is inhibited by progesterone, pointing out to the participation of a Gsa type of G-protein (Jordana et al, 1981a(Jordana et al, , 1984Sadler and Maller, 1981).…”
mentioning
confidence: 95%
“…Progesterone, through an unknown non genomic mechanism, triggers the maturation process Godeau et al, 1978;Masui and Clarke, 1979), which involves reduction of oocyte cAMP levels through adenylyl cyclase (AC) inhibition (Maller and Krebs, 1977;Bravo et al, 1978;Maller et al, 1978;Schorderet-Slatkine et al, 1978SchorderetSlatkine and Baulieu, 1982;Jordana et al, 1984). Progesterone induced AC inhibition has been shown to be GTP-dependent, and requires the participation of a Pertussis toxin insensitive G-protein (Jordana et al, 1981a(Jordana et al, ,b, 1984Sadler and Maller, 1981;Goodhardt et al, 1984;Olate et al, 1984Olate et al, , 1985Sadler et al, 1984). Activation of AC by different G-protein stimulators such as Gpp(NH)p, GTPgS, aluminum fluoride, and Cholera toxin, is inhibited by progesterone, indicating the participation of Gas in steroid action (Jordana et al, 1981a(Jordana et al, , 1984Sadler and Maller, 1981;Antonelli et al, 1986;Gallo et al, 1995).…”
mentioning
confidence: 96%
“…Recently, it has been demonstrated that the yeast homolog of p21 has direct effects upon intracellular levels of cyclic AMP and that GTP-dependent adenylate cyclase activity in yeast cells requires a normal ras genotype (27) otide exchange (16,17,18). However, in contrast to hormonal inhibition of adenylate cyclase in other cell systems, inhibition of oocyte adenylate cyclase by progesterone is not mediated via the inhibitory guanine-nucleotide-binding subunit, G1, in the conventional manner (7,14,19). To determine whether p21 might be involved in the regulation of oocyte cell division, antibodies to p21 were microinjected into oocytes, and subsequent changes in the time course of progesterone-induced GVBD were monitored.…”
mentioning
confidence: 99%